Sleep disorders among healthcare workers during the COVID-19 pandemic: An umbrella review and meta-analysis - Somayeh Tahernejad; Sina Ghaffari; Hojjat Farahmandnia; Iman Farahi-Ashtiani; Ali Sahebi; Azadeh Tahernejd (Nursing Practice Today, 2023)
Background & Aim: Healthcare workers are at the forefront of the fight against COVID-19 and are exposed to numerous risks and health consequences, including sleep disturbance. The present study aimed to investigate the prevalence of sleep disorders among HCWs during the COVID-19 pandemic using an umbrella review of meta-analyses. Methods & Materials: Based on the guidance of PRISMA, literature was searched on the Web of Science, PubMed, Embase, Science Direct, Scopus, and Google Scholar (from the beginning of January 2020 to the end of March 2022). The random effects model was used for meta-analysis, and the I2 index was employed to ascertain heterogeneity among studies. Publication bias was investigated using the Begg test. Data were analyzed using STATA software version 14. Results: Initially, 561 studies were found after the primary literature search in the data resources, of which 27 eligible studies were selected for quality assessment and data extraction. The results showed that the prevalence of sleep disorders among HCWs during the COVID-19 pandemic was 38.27% (95% CI: 35.20-41.01, I2= 74.2%, P= 0.008). Conclusion: Based on the results of this review, the prevalence of sleep disorders among HCWs during the COVID-19 pandemic was relatively high. Therefore, these individuals should undergo routine screening for sleep quality and other mental health disorders.